Efficient Reduction of Nitroarenes Catalyzed by Graphene-Based Magnetic Nanocomposite - Zhang, Hai-Yan; Feng, Cheng; Shang, Ning-Zhao; Gao, Shu-Tao; Wang, Chun; Wang, Zhi (Letters in Organic Chemistry, 2013)
In this paper, a superparamagnetic graphene-Fe3O4 nanocomposite (G-Fe3O4) was synthesized by a coprecipitation method, which was used as an efficient catalyst for the reduction of nitroarenes with hydrazine hydrate for the first time. The method has been applied on a broad range of compounds with different properties. The G-Fe3O4 catalyst can be readily recovered and reused without a significant loss of catalytic activity.
Keywords: coprecipitation